Peru : Drivers of De-dollarization - Garcia-Escribano, Mercedes (IMF Working Papers; Working Paper, 2010)
Peru has successfully pursued a market-driven financial de-dollarization during the last decade. Dollarization of credit and deposit of commercial banks - across all sectors and maturities - has declined, with larger declines for commercial credit and time and saving deposits. The analysis presented in this paper confirms that de-dollarization has been driven by macroeconomic stability, introduction of prudential policies to better reflect currency risk (such as the management of reserve requirements), and the development of the capital market in soles. Further de-dollarization efforts could focus on these three fronts. Given the now consolidated macroeconomic stability, greater exchange rate flexibility could foster de-dollarization; additional prudential measures could further discourage banks' lending and funding in foreign currency; while further capital market development in domestic currency would help overall financial de-dollarization.